2016
DOI: 10.1038/srep29638
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive detection of animal nerve impulses with an atomic magnetometer operating near quantum limited sensitivity

Abstract: Magnetic fields generated by human and animal organs, such as the heart, brain and nervous system carry information useful for biological and medical purposes. These magnetic fields are most commonly detected using cryogenically-cooled superconducting magnetometers. Here we present the first detection of action potentials from an animal nerve using an optical atomic magnetometer. Using an optimal design we are able to achieve the sensitivity dominated by the quantum shot noise of light and quantum projection n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 21 publications
2
62
0
Order By: Relevance
“…Vapor cells have been miniaturized to few mm 3 small volumes (Shah et al, 2007) and have been used to demonstrate entanglement-enhanced sensing (Fernholz et al, 2008;Wasilewski et al, 2010). The most advanced application of vapor cells is arguably the detection of neural activity (Jensen et al, 2016;Livanov et al, 1978), which has found use in magnetoencephalography (Xia et al, 2006). Vapor cells also promise complementary access to high-energy physics, detecting anomalous dipole moments from coupling to exotic elementary particles and background fields beyond the standard model (Pustelny et al, 2013;Smiciklas et al, 2011;Swallows et al, 2013).…”
Section: Atomic Vaporsmentioning
confidence: 99%
“…Vapor cells have been miniaturized to few mm 3 small volumes (Shah et al, 2007) and have been used to demonstrate entanglement-enhanced sensing (Fernholz et al, 2008;Wasilewski et al, 2010). The most advanced application of vapor cells is arguably the detection of neural activity (Jensen et al, 2016;Livanov et al, 1978), which has found use in magnetoencephalography (Xia et al, 2006). Vapor cells also promise complementary access to high-energy physics, detecting anomalous dipole moments from coupling to exotic elementary particles and background fields beyond the standard model (Pustelny et al, 2013;Smiciklas et al, 2011;Swallows et al, 2013).…”
Section: Atomic Vaporsmentioning
confidence: 99%
“…For slowly varying signals, the transition frequency of the sensor can be tracked in real time [13], permitting detection of arbitrary waveforms in a single shot. By using a large ensemble of quantum sensors detection bandwidths of up to ∼ 1 MHz have been demonstrated [14,15], with applications in MRI tomograph stabilization [14], neural signaling [16,17], or magnetoencephalography [18].For rapidly changing signals the waveform can no longer be tracked, and a general waveform cannot be recorded in a single shot. However, if a waveform is repetitive or can be re-triggered, multiple passages of the waveform can be combined to reconstruct the full waveform signal.…”
mentioning
confidence: 99%
“…Schematic sideviews of single-membrane (a) and doublemembrane (b) resonators. c) Photograph of a double-membrane resonator.ing for realizing integrated micromechanical cells for pressure sensing and ultrasound transduction applications [26], spectroscopy [27] or for collective and hybrid optomechanics [28][29][30][31][32].A schematic of the suspended membrane drums used in this work is shown in Fig. 1.…”
mentioning
confidence: 99%